Penurunan Stigma ODGJ Melalui Kearifan Lokal Bali: Tat Twam Asi - Muryani, Ni Made Sri; Artawan, I Kadek; Sarjana, I Putu (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2023)
Background: Bali Province is in first place with 11% of schizophrenia sufferers. Mental disorders in Bali are also often associated with possession by demons, evil spirits, or curses from ancestors. Bali is known to have various cultures and local wisdom that bind its people, one of which is Tat Twam Asi which means you are me and I am you. Objective: The aim of this activity is to reduce the stigma of people with mental disorders through the application of Tat Twam Asi. Method: This activity was carried out by providing health education about the application of Tat Twam Asi in Mental Health with a total of 180 participants. Before health education is carried out, participants complete a pre-test and a post-test is given after completing the education. There are five questions in the pre-test and post-test with the criteria for a good score of ³ 75%, a fair score of 56 – 74% and a poor score of <55%. Results: Based on the results of the pre-test carried out before the health education, the average participant score was <55% in the poor category. After providing health education about the application of Tat Twam Asi in mental health, the average participant score was  ³ 75% in the good category. Conclusion: Based on the results of community activities, it was found that there was an increase in public knowledge about the application of Tat Twam Asi in mental health, as an effort to reduce stigma towards people with mental disorders.